1994
DOI: 10.1111/j.1439-0264.1994.tb00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Pituitary‐Thyroid Axis in Bilaterally Adrenalectomized or Adrenal Transplanted Rats

Abstract: The percentage, distribution, shape, intensity of staining and morphometrical parameters of the pituitary TSH immunoreactive cells and the histological features of the thyroid glands, were compared between adult rats with intact adrenals, without adrenals and biadrenalectomized animals with neonatal adrenal grafts. After the removal of the adrenal glands, TSH immunoreactive cells increased in percentage and exhibited a higher complexity of the cellular outline, than that of the intact animals. The nuclear, cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The average nuclear size in pituitary cells (which reflects their functional state) is known to be changed due to perturbations in hormonal status [40-42]. Although the average nuclear size from pituitaries of DES-treated or phytoestrogen-treated animals showed no difference compared to cholesterol-treated control animals, the observed changes in nuclear size heterogeneity with DES (and especially with DES in combination with all phytoestrogens), suggested that the functions of pituitary cells had been altered.…”
Section: Discussionmentioning
confidence: 99%
“…The average nuclear size in pituitary cells (which reflects their functional state) is known to be changed due to perturbations in hormonal status [40-42]. Although the average nuclear size from pituitaries of DES-treated or phytoestrogen-treated animals showed no difference compared to cholesterol-treated control animals, the observed changes in nuclear size heterogeneity with DES (and especially with DES in combination with all phytoestrogens), suggested that the functions of pituitary cells had been altered.…”
Section: Discussionmentioning
confidence: 99%
“…(1972) reported that TSH cells in the rat are more prominent in the ventral and middle part of the lateral section of pars distalis and rare in its dorsal. Sarria et al. (1994) reported that these cells are found single or in small groups widely along the pars distalis.…”
Section: Discussionmentioning
confidence: 98%
“…Different ideas on localization of TSH cells are propound. While Sarria et al (1994) reported that these cells are found as single or in small groups distributed widely along the pars distalis, Baker et al. (1972) observed them generally in the ventral and middle part of the lateral section of the pars distalis and in lesser extent in its dorsal regions.…”
Section: Introductionmentioning
confidence: 98%